The Preparedness Level of Families with Disabilities Children in Facing the Earthquake and Tsunami Disaster in Padang, West Sumatra - Muchsin Riviwanto; Darwel Darwel; Defriani Dwiyanti; Juanda Juanda (International Journal of Disaster Management, 2021)
Disability groups are groups vulnerable to disaster risk. Most families with disabilities feel worried about defending themselves in the event of a disaster. They are less socialized with disaster mitigation efforts. This research has provided an overview of the preparedness of families with disabilities children in increasing disaster resilience. Analytical research was conducted on families with disabilities children in the city of Padang. Data collection tools in this study used a standard questionnaire from LIPI-UNESCO / ISDR. The data were processed by a computer and analyzed using multiple regression statistical tests. The results showed the preparedness of Families With Disabilities Children in the face of disasters; it was seen that the knowledge category was ready (42.2%), the preparedness plan category was not ready (37.8%), the disaster warning category was not ready (46.7%), the resource mobilization category was not ready, ready (82.2%), the tsunami disaster preparedness index value is 57% (ready category). This research recommended local governments must provide special treatment for people with disabilities by increasing training, seminars, and disaster simulations.